IAA-producing plant growth promoting rhizobacteria from Ceanothus velutinus enhance cutting propagation efficiency and Arabidopsis biomass - Ganesh, Jyothsna; Hewitt, Katherine; Devkota, Ananta Raj; Wilson, Ty; Kaundal, Amita (Frontiers in Plant Science, 2024)
Climate-induced drought impacts plant growth and development. Recurring droughts increase the demand for water for food production and landscaping. Native plants in the Intermountain West region of the US are of keen interest in low water use landscaping as they are acclimatized to dry and cold environments. These native plants do very well at their native locations but are difficult to propagate in landscape. One of the possible reasons is the lack of associated microbiome in the landscaping. Microbiome in the soil contributes to soil health and impacts plant growth and development. Here, we used the bulk soil from the native plant Ceanothus velutinus (snowbrush ceanothus) as inoculant to enhance its propagation. Snowbrush ceanothus is an ornamental plant for low-water landscaping that is hard to propagate asexually. Using 50% native bulk soil as inoculant in the potting mix significantly improved the survival rate of the cuttings compared to no-treated cuttings. Twenty-four plant growth-promoting rhizobacteria (PGPR) producing indole acetic acid (IAA) were isolated from the rhizosphere and roots of the survived snowbrush. Seventeen isolates had more than 10µg/mL of IAA were shortlisted and tested for seven different plant growth-promoting (PGP) traits; 76% showed nitrogen-fixing ability on Norris Glucose Nitrogen free media,70% showed phosphate solubilization activity, 76% showed siderophore production, 36% showed protease activity, 94% showed ACC deaminase activity on DF-ACC media, 76% produced catalase and all of isolates produced ammonia. Eight of seventeen isolates, CK-6, CK-22, CK-41, CK-44, CK-47, CK-50, CK-53, and CK-55, showed an increase in shoot biomass in Arabidopsis thaliana. Seven out of eight isolates were identified as Pseudomonas, except CK-55, identified as Sphingobium based on 16S rRNA gene sequencing. The shortlisted isolates are being tested on different grain and vegetable crops to mitigate drought stress and promote plant growth.